Defining social inclusion of people with intellectual and developmental disabilities: An ecological model of social networks and community participation - Simplican, Stacy Clifford; Leader, Geraldine; Kosciulek, John; Leahy, Michael (Research in developmental disabilities, 2015)
•Our review of social inclusion literature finds several conflicting definitions.•Hence, we propose a definition and ecological model of social inclusion.•Our definition focuses on interpersonal relationships and community participation.•Our ecological model includes individual, interpersonal, and community variables.•We describe future research that our definition and ecological model can inform. Social inclusion is an important goal for people with intellectual and developmental disabilities, families, service providers, and policymakers; however, the concept of social inclusion remains unclear, largely due to multiple and conflicting definitions in research and policy. We define social inclusion as the interaction between two major life domains: interpersonal relationships and community participation. We then propose an ecological model of social inclusion that includes individual, interpersonal, organizational, community, and socio-political factors. We identify four areas of research that our ecological model of social inclusion can move forward: (1) organizational implementation of social inclusion; (2) social inclusion of people with intellectual and developmental disabilities living with their families, (3) social inclusion of people along a broader spectrum of disability, and (4) the potential role of self-advocacy organizations in promoting social inclusion.